ANALISIS PENERAPAN D’JOS DI PROVINSI DKI JAKARTA DENGAN PENDEKATAN TECHNOLOGY ACCEPTENCE MODEL (TAM) STUDI KASUS BPKD: ANALYSIS OF THE IMPLEMENTATION OF D’JOS IN DKI JAKARTA PROVINCE USING THE TECHNOLOGY ACCEPTANCE MODEL (TAM): A CASE STUDY AT THE REGIONAL FINANCIAL MANAGEMENT AGENCY (BPKD) - Achmad Farhan; Ifan Junaedi; Anton Zulkarnain Sianipar (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
This study analyzes the implementation of the Deposito Jakarta Online System (D’JOS) application at the Regional Financial Management Agency (BPKD) of DKI Jakarta Province as part of efforts to digitalize regional financial management based on the principles of Good Governance. The approach used is descriptive qualitative, with data collected through interviews, direct observations, and document studies. The analysis is conducted using the Technology Acceptance Model (TAM) framework, which includes five main aspects: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), Behavioral Intention to Use (BI), and Actual Use (AU). The results indicate that the D’JOS application is perceived as beneficial in improving the efficiency, accuracy, and transparency of deposit management. A total of 85% of users stated that D’JOS has facilitated their work, particularly in financial reporting and monitoring. Users also reported ease of use and expressed positive attitudes and strong intentions to continue using the system sustainably. In practice, the system has been consistently utilized in BPKD’s daily operational activities. Therefore, D’JOS has proven to support digital transformation in regional financial governance and has the potential to be replicated by other local governments. This study recommends the development of additional features such as automatic notifications, stronger data security, and system integration, as well as the establishment of specific regulations, such as a Governor's Decree, to support the standardization and sustainability of D’JOS usage within the DKI Jakarta Provincial Government.